Does Self-Employment Pay? The Role of Unemployment and Earnings Risk - Joaquin Garcia-Cabo; Rocio Madera (CESifo GmbH, 2024)
This paper documents the role of unemployment and earnings risk in reconciling evidence in payoff differentials between self-employment and paid-employment. Using Spanish administrative data, we characterize the distribution and dynamics of earnings and document lower and less dispersed earnings in self-employment. We consider alternative hypotheses and highlight the role of lower unemployment risk in self-employment. We decompose earnings risk dynamics by estimating a life-cycle earnings process. Indeed, the self-employed experience lower returns but also face lower volatility and persistence of shocks throughout their life-cycle. Our results challenge the conventional view that self-employment necessarily entails higher risk and highlight that accounting for differences in labor earnings risk is important to reconcile the payoff differentials between self-employment and paid-employment.
Keywords: J24; J31; J41; 330; self-employment; segmented labor markets; earnings risk; income process